Diseño de un Sistema de Comunicación Óptico - Inalámbrico orientado al análisis comparativo entre las tecnologías Free Space Optics (FSO) y Radiofrecuencia (RF) - Torres Rojas, Jhandry Sergio (2023)
In today's wireless communications systems, there are several requirements that play a key role in achieving good network performance. Flexibility and cost-effectiveness in service provisioning have led to an imbalance also known as the "last mile bottleneck". Free space optical communications (FSO) is one of the viable alternatives and one of the most optimal solutions taking into account bandwidth, implementation time, data transmission with high speeds, cost-effectiveness and security. In this degree work, research about Free Space Optics technology was performed, investigating from its origins to the present, highlighting the great benefits as well as limitations of this technology compared to other wireless technologies. Once the first phase was completed, a scenario in the city of Loja was used as a reference to design and simulate a point-to-point link for FSO technology and Radio Frequency (RF) technology. The configuration values for each technology were given thanks to the technical specifications of each selected equipment shown in the development of this work. A series of simulations and mathematical calculations were executed where the results obtained allow understanding under which atmospheric conditions an optimal link and a misguided link with failures are available. For FSO, 10 scenarios are presented since it is the main subject of study and for RF, only one scenario is shown, which offers several results for analysis. A comparative analysis of both technologies was made in order to show the strengths of FSO over RF, and an economic analysis is also detailed in terms of approximate costs involved in implementing each technology. The aim of this thesis work is to provide the reader with a theoretical, practical and mathematical knowledge of FSO technology, to take advantage of new technologies that are used in technologically developed countries, since in our locality they have been isolated and little studied. Key words: free space optics, bandwidth, attenuation, wavelength, transmission power